Citraconic acid and its anhydride-based hetero-Diels–Alder reactions in the synthesis of new thiopyrano[2, 3-d][1, 3]thiazole derivatives. Issue 6 (19th March 2021) - Zelisko, Nataliya; Karpenko, Olexandr; Muzychenko, Volodymyr; Gzella, Andrzej; Lesyk, Roman
Abstract: Novel rel -(5 R, 5a R, 11b S )-5-methyl-2, 6-dioxo-3, 5a, 6, 11b-tetrahydro- 2H, 5H -chromeno[4΄, 3΄:4, 5]thiopyrano[2, 3- d ][1, 3]thiazole-5-carboxylic acids were synthesized in 63–72% yields via tandem acylation -hetero -Diels–Alder reaction of 5-(2-hydroxybenzylidene)-4-thioxo-2-thiazolidinones with citraconic acid and its anhydride. The regio- and stereochemistry of the process was confirmed by NMR spectral data and a single-crystal X-ray diffraction analysis. Graphical Abstract: UF0001